The Quran Concept of Law Enforcement Environmental Damage - Andi Marlina; Andi Muliyono (Budapest International Research and Critics University, 2022)
The purpose of this research is to analyze the factors that cause environmental damage in the study of the Qur'an and the principles of environmental management based on the concept of the Qur'an. The research method used is a normative research method with a comparative approach (Comparative Approach), a conceptual approach (Conceptual Approach Approach) and an analytical approach). (Analytical approaches). The results of the study indicate that environmental damage, which in Al-Quran terms is called Fasad, occurs because it is caused by human actions that are wrong in managing and utilizing natural resources. Humans have come out of the guidance of the Qur'an in maintaining and preserving the environment. As in the Qur'anic concept that environmental management must be carried out with the principle of compassion.